Communicating and Understanding Ecosystem Services Assessment With Coastal Stakeholders: Obstacles and Opportunities - DeLorme, Denise E.; Stephens, Sonia H.; Collini, Renee C.; Yoskowitz, David W.; Hagen, Scott C. (Frontiers in Communication, 2021)
This paper reports on insights and lessons learned from stakeholder engagement, particularly focus groups, conducted during a multi-year, NOAA-sponsored transdisciplinary project. A major project goal was to demonstrate and communicate benefits of natural and nature-based features (NNBFs) (e.g., barrier islands, dunes, and marshes) in the Northern Gulf of Mexico region through the lens of economic impacts and ecosystem services. Overall, the findings indicate economic impacts and ecosystem services can be challenging topics to communicate because of complexity in conceptualization and valuation. From our experiences, we recommend using “ecosystem services assessment” (ESA), a more encompassing, accurate, and understandable term to stakeholders. ESA recognizes the integrated human (or built) and natural ecosystem and holistic benefits provided by and to both. The paper concludes with a discussion of future research opportunities for improving ESA-oriented science and outreach.